Pengaturan Tindak Pidana Perkosaan Dalam Perkawinan Menurut Hukum Pidana Indonesia Dan Hukum Pidana Singapura - Fragma Sari, Trachel; Mulyati, Nani; Elvandari, Siska (Delicti : Jurnal Hukum Pidana Dan Kriminologi, 2024)
In Indonesia although marital rape is not specifically definedm there are laws and regulations that govern this issue. Similarly Singapore regulated rape in a broader sense. In singapore, rape is a crime for which an arrest can be made without a warrant. Under the singapore penal code prior to its amandment, rape by a husband against his wife was not recognized as a crime except under certain conditions. The research problem formulated in this study is the regulation of the crime of marital rape under Indonesia and singapore penal code. The research method used to discuss and analyze this issue is normative legal research whit a statutory approach and comparative approach. The results of the study show that the regulation of marital rape in Indonesia can be found in the law on the elimination of domestic violance (uu pkdrt), law on sexual violance crimes (uu tpks), and the national criminal code. Meanwhile, singapore regulation regarding marital rape can be found in section 375 act 15 of 2019 of the singapore penal code. The fundamental difference in the regulation of marital rape between the two countries lies in the subjects and objects related to the crime. In Indonesia, there is generally no distinction between the subject and object based on gender. In contrast, Singapore recognizes only males as potential perpetrators and females as potential victims. Neother ondonesia nor singapore provides a clear definition of marital rape, however, both countries recognize that forced sexual intercourse contitutes a crime